Exploring Teachers’ and Students’ Perceptions of Deep Learning: Integrating Meaningful, Mindful, and Joyful Learning in ELT Classrooms - Dea Amanda Ricita; Abdul Halim; Sunarti, Sunarti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study investigates teachers’ and students’ perceptions of deep learning within English Language Teaching (ELT) classrooms at SMK Negeri 15 Samarinda, focusing on the integration of meaningful, mindful, and joyful learning strategies. Employing a mixed-methods design, the research collected quantitative data through Likert-scale questionnaires from 66 students and 5 teachers, and qualitative data through semi-structured interviews with the same group of teachers. Quantitative results showed generally positive perceptions, with students reporting an average score of 3.17 on deep learning indicators. Notably, 86.3% strongly agreed that games and storytelling increased motivation, highlighting the value of joyful learning. Qualitative findings revealed key challenges, including limited infrastructure, inconsistent digital literacy, and curriculum constraints. However, teachers demonstrated adaptability through real-world projects, collaborative strategies, and reflective discipline. Despite minimal formal training, many educators intuitively applied deep learning principles. The study underscores the need for systemic support such as professional development and equitable resource allocation to ensure the effective and sustainable integration of deep learning in ELT practices.